Nickel-Catalyzed Homocoupling of (Z)-β-Iodoenol Esters: Stereoselective Access to (Z,Z)-Buta-1,3-diene-1,4-diyl Diesters - Francos, Javier; Cadierno, Victorio (Synthesis, 2019)
A straightforward and broad-scope procedure to obtain symmetrically substituted buta-1,3-diene-1,4-diyl diesters, based on the homocoupling of the corresponding (Z)-β-iodoenol esters, is presented. It involves the use of a catalytic system composed of [NiCl2(PPh3)2] (10 mol%), NaI (10 mol%), and excess of Zn dust. The reactions proceed in THF at room temperature with exquisite preservation of the stereochemistry of the C=C bond of the starting iodoolefins, thus leading to the final dienes as the corresponding Z,Z-stereoisomers exclusively.
Keywords: homocoupling reactions; nickel; iodoalkenes; buta-1,3-dienes; enol esters; diesters